2011
DOI: 10.1007/978-3-642-20525-5_5
|View full text |Cite
|
Sign up to set email alerts
|

On the Design of Boolean Network Robots

Abstract: Abstract. Dynamical systems theory and complexity science provide powerful tools for analysing artificial agents and robots. Furthermore, they have been recently proposed also as a source of design principles and guidelines. Boolean networks are a prominent example of complex dynamical systems and they have been shown to effectively capture important phenomena in gene regulation. From an engineering perspective, these models are very compelling, because they can exhibit rich and complex behaviours, in spite of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…Instances of POBDSs abound in fields such as genomics [12], robotics [13], digital communication systems [14], and more. The optimal recursive minimum mean-square error (MMSE) state estimators for this model are called the Boolean Kalman Filter (BKF) [1] and the Boolean Kalman Smoother (BKS) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Instances of POBDSs abound in fields such as genomics [12], robotics [13], digital communication systems [14], and more. The optimal recursive minimum mean-square error (MMSE) state estimators for this model are called the Boolean Kalman Filter (BKF) [1] and the Boolean Kalman Smoother (BKS) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Results are shown in Figure 2. As we can observe, cluster {1, 3,5,8,10,12,18} has a higher set- 3,5,7,8,10,12,18} compared with the set-influence of random clusters of the same size (averaged over 100 random clusters)…”
Section: Networkmentioning
confidence: 93%
“…BNs are extremely interesting from an engineering perspective because of their ability to display complex and rich dynamics, despite the compactness of their description. In a previous work, it has been shown that BNs can be used to control robots [12].…”
Section: Bn-robot Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The engineering-oriented applications of Boolean networks in the literature include biomedical applications such as modeling and potentially influencing the progression of a cellular-level disease (Datta et al, 2003;Datta et al, 2004;Pal et al, 2006;Shmulevich et al, 2002b). There are also applications in artificial intelligence and robotics where Boolean networks are used as a decision-making or dedicated control subsystem (Bongard, 2011;Garattoni et al, 2013;Paczuski et al, 2000;Roli et al, 2011;Vichi et al, 2012). In both of these application types, the use of Boolean networks is limited to modeling the target system as a Boolean network or using a Boolean network as a foundational component in the design of a system.…”
Section: Introductionmentioning
confidence: 99%